Structure-activity study of LVV-hemorphin-7: angiotensin AT4 receptor ligand and inhibitor of insulin-regulated aminopeptidase - Lee, Joohyung; Mustafa, Tomris; McDowall, Sharon G; Mendelsohn, Frederick A O; Brennan, Michelle; Lew, Rebecca A; Albiston, Anthony L; Chai, Siew Yeen (The Journal of pharmacology and experimental therapeutics, 2003)
The decapeptide LVV-hemorphin-7 binds with high affinity to the angiotensin IV (Ang IV) receptor (AT(4) receptor), eliciting a number of physiological effects, including cellular proliferation and memory enhancement. We have recently shown that the AT(4) receptor is identical to insulin-regulated aminopeptidase (IRAP) and that both LVV-hemorphin-7 and Ang IV inhibit the catalytic activity of IRAP. In the current study, a series of alanine-substituted and N- or C-terminally modified analogs of LVV-hemorphin-7 were evaluated for their abilities to compete for (125)I-Ang IV binding in sheep adrenal and cerebellar membranes. Selected analogs were also analyzed for binding to recombinant human IRAP and inhibition of IRAP aminopeptidase activity. C-Terminal deletions of LVV-hemorphin-7 resulted in modest changes in affinity for IRAP, whereas deletion of the first three N-terminal residues abolished binding. Monosubstitutions of Tyr(4) and Trp(6) with alanine resulted in a 10-fold reduction in affinity. Competition binding studies using recombinant human IRAP demonstrated the same rank order of affinity as obtained for the ovine tissues. All LVV-hemorphin-7 analogs tested, except for Leu-Val-Val-Tyr, inhibit the cleavage of the synthetic substrate, leucine beta-naphthylamide, by IRAP, with K(i) values between 56 and 620 nM. We find that the Val(3) residue is crucial for LVV-hemorphin-7 binding to IRAP, whereas the C-terminal domain seems to play a minor role. The current study highlights the minimal residues necessary for binding and inhibition of IRAP and provides a basis to design peptidomimetic analogs for experimental and potentially clinical use.